Back Massage Relaxation Therapy Intervention and Measurement of Client Fatigue Score in Congested Heart Failure Clients with Activity Intolerance Disorder - Iif Taufiq El Haque; Asep Gunawan; Nur Hidayat; Sukmara Aji Falah (LPPM STIKes Muhammadiyah Ciamis, 2022)
Objective: Congestive heart failure is a condition where the heart is unable to pump adequate blood to meet the needs of the network. If the supply in the blood cannot flow to parts of the body, it can cause the body to experience weakness, lethargy, and usually tire easily, so that it will experience problems, namely activity intolerance. One of the non-pharmacological interventions that can be done is relaxation therapy, one of which is back massage therapy, and measuring fatigue scores. This study was conducted to present nursing care to congestive heart failure clients with activity intolerance problems with back massage interventions and to measure client fatigue scores in the Kenanga Room at Banjar City Hospital. Method: The method in this study is a descriptive case study and a subjective questionnaire that aims to describe the nursing care of congestive heart failure clients with activity intolerance disorders with back massage interventions and measure fatigue scores using FACIT (Functional Assessment of Chronic Illness Therapy) questionnaires for clients in the memory room of RSUD Kota Banjar. The approach used in this case study is the process of nursing care, which includes assessment, intervention, diagnosis, implementation, and evaluation of nursing. Data collection techniques include interviews, observation, physical examination, and documentation studies. Subjects in this study were patients who experienced congestive heart failure with activity intolerance problems. Result: At the assessment stage, it is known that the client complains that the body is tired easily. The intervention given is energy management according to the SIKI book, and adding back massage therapy and measuring the client's fatigue score are carried out for 3 days. After the intervention was carried out, the client said that he was tired, and the client's fatigue score had increased. Conclusion: Nursing care for clients who experience congestive heart failure with activity intolerance problems using back massage therapy is effective in overcoming client fatigue.